Nondestructive testing of railway embankments by measuring multi-modal dispersion of surface waves induced by high-speed trains with linear geophone arrays - José Cunha Teixeira; Ludovic Bodet; Marine Dangeard; Alexandrine Gesret; Amélie Hallier; Agnès Rivière; Audrey Burzawa; Julio José Cárdenas Chapellín; Marie Fonda; Ramon Sanchez Gonzalez; Amine Dhemaied; Joséphine Boisson Gaboriau (Seismica)
To effectively address engineering challenges and risks, it is crucial to characterize mechanical properties of near-surface environments. The Multichannel Analysis of Surface Waves (MASW) has proven to be a valuable active seismic imaging technique by providing near-surface shear (S)-wave velocities estimations. However, its application to urban areas requires further development. This study leverages well-constrained experimental sites to assess the viability of a passive-MASW technique, utilizing seismic waves induced by high-speed train traffic instead of conventional active sources. We suggest employing short 96-geophone uniform linear arrays to capture surface waves in a broad frequency band (10-200 Hz). Train passages are automatically detected and categorized regarding to the train travel direction. Seismic interferometry and phase-weighted stack techniques are applied to generate virtual shot-gathers that are transformed into high-resolution multi-modal dispersion images. Our results demonstrate a strong coherence between the picked dispersion curves from the passive-MASW approach and those obtained through traditional active MASW with a hammer source. We discuss the validity of higher modes and explore array density limits to ensure reliable results. Our findings highlight that seismic interferometry, coupled with a high phase-weighted stack power, effectively recovers energy at high frequencies, enhancing the characterization of multi-modal surface-wave dispersion associated with thin near-surface layers.